Solution-phase, template-free synthesis of PbI2 and MAPbI3 nano/microtubes for high-sensitivity photodetectors. Issue 12 (11th March 2019) - Chandrasekar, Perumal Veeramalai; Yang, Shengyi; Hu, Jinming; Sulaman, Muhammad; Shi, Yuansheng; Saleem, Muhammad Imran; Tang, Yi; Jiang, Yurong; Zou, Bingsuo
Abstract : Solution-phase, template-free synthesis of PbI2 and MAPbI3 nano/microtubes and their applications in high-sensitivity photodetectors are presented. Abstract : Organic–inorganic hybrid perovskite materials with exotic semiconducting properties have become inevitable candidates for next-generation electronic devices. Very recently, a low dimensional nanostructure of the perovskite materials has attracted the scientific community due to its enhanced performance in optoelectronics as compared to its bulk counterparts. Herein, a facile method was developed for the scalable, room-temperature synthesis of CH3 NH3 PbI3 (MAPbI3 ) nano/microtubes by direct conversion of lead iodide (PbI2 ) microtubes through a solution-phase method. At first, the PbI2 microtubes were synthesized by the anti-solvent crystallization process and subsequently converted to CH3 NH3 PbI3 nano/microtubes by the addition of CH3 NH3 I (MAI) precursor directly in the solution phase. The corresponding photodetectors (PDs) in the lateral metal–semiconductor–metal (MSM) configuration of the PbI2 microtubes and MAPbI3 nano/microtubes on glass substrates were investigated systematically. Compared to the PbI2 based PDs (557 mA W −1, 3.65 × 10 12 Jones, 0.251 s/0.252 s), the MAPbI3 based PDs exhibit higher photoresponsivity, specific detectivity, and faster response time (25 A W −1, 9.9 × 10 13 Jones, 49 ms/20 ms) under irradiation with 4.6 μW cm −2 intensity light of the 532 nm laser at a bias of 5 V. The proposed method is a low-temperature process, easy to apply in large scale synthesis, and finds potential applications in optoelectronic devices.